Navigating Self-Reflection for Aspiring Special Education Teachers: A Scoping Review on Inclusive Educational Practices and Their Insights for Autism Education - Kamilla Klefbeck (MDPI AG, 2023)
This scoping review investigates the pivotal role of self-reflection in enhancing the skills of prospective educators, with the intention of drawing conclusions on how this aspect can contribute to improved teaching for students with autism. Two guiding research questions include: (1) How do targeted strategies in teacher education influence self-reflection among prospective special education teachers, and to what extent do these strategies enhance their reflective capacity, as indicated by the reviewed studies? (2) What research gaps exist regarding integrating reflective practice into teacher education programs to enhance prospective special education teachers' self-reflection and professionalism? Finally, conclusions drawn from the results are analyzed through the framework of core aspects defined in the ICD-11, the eleventh edition of the 'International Classification of Diseases'. This approach provides insight into how the conclusions can be applied to nurture self-reflection of future special education teachers, particularly emphasizing the facilitation of participation and learning for students with autism. Utilizing a scoping review methodology, the study comprehensively explores this vital area, adapting search strategies as needed. Several of the included studies suggested that to effectively contribute to the development of well-considered action strategies in encounters with students in a special education context, including autism education, it is not enough to incorporate reflective practice; the teacher candidates also need feedback and guidance. In conclusion, this research underscores self-reflection's pivotal role in bridging theory and practice, enhancing the preparation of future educators for their work with diverse student populations.